2013
DOI: 10.5352/jls.2013.23.6.757
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Statistical Optimization of Cultural Conditions for Mass Production of Carboxymethylcellulase by a Newly Isolated Marine Bacterium, Bacillus velezensis A-68 from Rice Hulls

Abstract: A microorganism producing carboxymethylcellulase (CMCase) was isolated from seawater, identified as Bacillus velezensis by analyses of 16S rDNA and partial sequences of the gyrA, and designated as B. velezensis A-68. The optimal conditions for production of CMCase by B. velezensis A-68 were established using response surface methodology (RSM). The optimal concentrations of rice hulls and yeast extract, and initial pH of the medium for cell growth were 60.2 g/l, 7.38 g/l, and 7.18, respectively, whereas those f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 30 publications
4
14
0
Order By: Relevance
“…The value of the adjusted determination coefficient (Adj. R 2 = 0.9229) was very high to advocate for a high significance of this model [26,27]. The predicted determination of coefficient of 0.8001 was in reasonable agreement with the Adj.…”
Section: Resultssupporting
confidence: 65%
“…The value of the adjusted determination coefficient (Adj. R 2 = 0.9229) was very high to advocate for a high significance of this model [26,27]. The predicted determination of coefficient of 0.8001 was in reasonable agreement with the Adj.…”
Section: Resultssupporting
confidence: 65%
“…Its value of the adjusted coefficient of determination (Adj. R 2 = 0.9442) was relatively high to advocate for this model's significance [26]. This model with the multiple correlation and adjusted coefficients indicated that the above equation was adequate for predicting the production of CMCase by E. coli KACC 91335P without shifts in optimal conditions of the agitation speed and/or aeration rate.…”
Section: Correlation Between Cells Growth and Its Production Of Cmcasementioning
confidence: 81%
“…Dry cell weight was measured as described previously Kim et al 2013). The activity of cellulase was measured by the 3,5-dinitrosalicylic acid (DNS) method (Kim et al 2012b).…”
Section: Methodsmentioning
confidence: 99%